Premature aging is associated with higher levels of 8‐oxoguanine and increased DNA damage in the Polg mutator mouse. Issue 9 (22nd August 2022) - Yu, Tenghui; Slone, Jesse; Liu, Wensheng; Barnes, Ryan; Opresko, Patricia L.; Wark, Landon; Mai, Sabine; Horvath, Steve; Huang, Taosheng
Abstract: Mitochondrial dysfunction plays an important role in the aging process. However, the mechanism by which this dysfunction causes aging is not fully understood. The accumulation of mutations in the mitochondrial genome (or "mtDNA") has been proposed as a contributor. One compelling piece of evidence in support of this hypothesis comes from the Polg D257A/D257A mutator mouse ( Polg mut/mut ). These mice express an error‐prone mitochondrial DNA polymerase that results in the accumulation of mtDNA mutations, accelerated aging, and premature death. In this paper, we have used the Polg mut/mut model to investigate whether the age‐related biological effects observed in these mice are triggered by oxidative damage to the DNA that compromises the integrity of the genome. Our results show that mutator mouse has significantly higher levels of 8‐oxoguanine (8‐oxoGua) that are correlated with increased nuclear DNA (nDNA) strand breakage and oxidative nDNA damage, shorter average telomere length, and reduced mtDNA integrity. Based on these results, we propose a model whereby the increased level of reactive oxygen species (ROS) associated with the accumulation of mtDNA mutations in Polg mut/mut mice results in higher levels of 8‐oxoGua, which in turn lead to compromised DNA integrity and accelerated aging via increased DNA fragmentation and telomere shortening. These results suggest that mitochondrial play a central role in aging and may guide future research to develop potential therapeutics for mitigating aging process. Abstract : The increased mtDNA mutation rate in the Polg mutator mouse has been previously shown to be associated with an accelerated aging phenotype, likely due to increased oxidative stress. This study provides evidence in support of this oxidative stress model by showing that the Polg mutation is also associated with increased levels of 8‐oxoGua as well as telomere shortening and other forms of DNA damage.